Institutional Mediation in Local Democracy: The Role of Legislative Secretariat in Facilitating Recess-Based Representation in Bali, Indonesia - Ni Putu Diah Sintya Dewi; Juwita Pratiwi Lukman (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This study examines the institutional role of the Legislative Secretariat in facilitating recess-based representation within the local democratic system in Bali, Indonesia. In Indonesia’s decentralized governance framework, legislative recess activities function as an important mechanism through which members of the Regional House of Representatives reconnect with their constituencies to absorb public aspirations and communicate policy developments. While existing studies on local political representation primarily emphasize elected representatives and electoral dynamics, the administrative institutions that support these interactions remain underexplored. This study addresses this gap by analyzing how the Session and Legislative Function Facilitation Division within the Bali Provincial Legislative Secretariat supports the planning, implementation, and reporting of recess activities, and how such administrative support contributes to the transmission of community aspirations into local policymaking processes. Using a qualitative descriptive approach, data were collected through in-depth interviews with legislative secretariat officials and staff, direct observation of administrative procedures, and document analysis of recess reports and institutional regulations. The findings indicate that the Secretariat plays a crucial mediating role across three stages: planning, implementation, and evaluation and reporting. Administrative coordination, technical guidance, and verification processes ensure that public aspirations gathered during recess activities are systematically documented and incorporated into policy deliberations. The study highlights the importance of bureaucratic capacity in strengthening democratic representation and effective state–society relations at the local level.